2014
DOI: 10.1128/jcm.03354-13
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Surveillance Reveals the Prevalence of Vibrio cholerae O139 Isolates in China from 1993 to 2012

Abstract: bVibrio cholerae serogroup O139 was first identified in 1992 in India and Bangladesh, in association with major epidemics of cholera in both countries; cases were noted shortly thereafter in China. We characterized 211 V. cholerae O139 isolates that were isolated at multiple sites in China between 1993 and 2012 from patients (n ‫؍‬ 92) and the environment (n ‫؍‬ 119). Among clinical isolates, 88 (95.7%) of 92 were toxigenic, compared with 47 (39.5%) of 119 environmental isolates. Toxigenic isolates carried the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
(31 reference statements)
3
14
0
Order By: Relevance
“…The PFGE patterns of the O139 strains differed from the profiles displayed by the O1 strains of clinical and environmental origin, which agreed with the presumption that the progenitor isolate of serogroup O139 in China was introduced from India 20 . Further research, such as whole genome sequencing, may help in understanding the origin of the O139 strains from Shandong Province 21 .…”
Section: Discussionsupporting
confidence: 62%
“…The PFGE patterns of the O139 strains differed from the profiles displayed by the O1 strains of clinical and environmental origin, which agreed with the presumption that the progenitor isolate of serogroup O139 in China was introduced from India 20 . Further research, such as whole genome sequencing, may help in understanding the origin of the O139 strains from Shandong Province 21 .…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, it is necessary to strength the surveillance of the O139 serogroup, which is experiencing this potential genetic shifting. A previous study indicated that toxigenic (cholera toxin produced) O139 isolates maintained a relatively high clonality, although isolates collected from widely different geographical locations were non-toxigenic isolates; however, the non-toxigenic isolates exhibited greater diversity and multiple clonal lineages [11]. This feature was also identified by PFGE of our local isolates in this study.…”
Section: Discussionsupporting
confidence: 72%
“…This has been previously shown for V. parahaemolyticus populations (Gonzalez-Escalona et al, 2008 ; Yan et al, 2011 ) and for V. cholerae populations. Zhang et al ( 2014 ) demonstrated that non-toxigenic isolates exhibited a greater diversity than did their toxigenic counterparts, suggesting that the acquisition of virulence factors and pathogenic behavior changes the population genetics of vibrios, probably by clonal selection and success during human infectious outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Beside investigation of vibriosis outbreaks (Chowdhury et al, 2004a ; Marin et al, 2013 ), several MLST studies on Vibrio spp. considered strain collections of very diverse geographical origins and thus gave a snapshot of the global structure of Vibrio populations (Octavia et al, 2013 ) or compared clinical and environmental populations (Teh et al, 2011 ; Yan et al, 2011 ; Theethakaew et al, 2013 ; Turner et al, 2013 ; Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%